Influence of pre-Andean history over Andean foreland deformation: structural styles in the Malargüe fold-and-thrust belt at 35ºS, Andes of Argentina - Mescua, Jose Francisco (2014)
We present the first complete balanced cross-section of the Argentinean Andes at 35ºS. Based on an extensive field survey and limited sub-surface information, we constructed a structural model in which both the tectonic inversion of Mesozoic normal faults and the formation of Cenozoic Andean thrusts play a role in the deformation. We obtained a shortening of 26.2 km, equivalent to 22% of the initial length. This value is lower than previous estimates obtained from partial cross-sections using non-inversion structural models. Comparison of our results with a geophysical model of the crust indicates that: (i) crustal thickness was not constant across the orogen before Andean shortening, but a thick (~45 km) crustal block was interpreted? in the west as a remnant of a Late Paleozoic orogeny, and a thinner sector (~32 km) was located in the east as a result of Mesozoic stretching; and (ii) the structural model presented in this work is more consistent with the regional shortening and crustal thickness trends than models which do not take into account tectonic inversion.